Prototype Sistem Monitoring Kualitas Air Rumah Tangga Dengan Memanfaatkan Internet of Things - Irawan, Etwin Hendri; Nurchim; Wijiyanto (Jurnal Inotera, 2024)
This research aims to develop a household water quality monitoring system using the Internet of Things (IoT) by monitoring water quality parameters such as pH, Total Dissolved Solids (TDS), turbidity, and temperature in real time. The prototyping method in the development of this system allows continuous interaction between developers and users to meet the needs of the system. Data is collected through literature studies and observations to support system development. The results of this study are that every 1 minute, the sensor data is sent to the server, and then the sensor data will be displayed on the web platform; if the sensor data value is not at the predetermined value limit according to Permenkes number 2 of 2023, the displayed value will be red. The data collected by the sensor is sent to the server built with Node.js and stored in the PostgreSQL database. The monitoring results will also be displayed on a 20x4 I2C LCD. The system successfully monitors water quality parameters in real time, with results displayed on a web platform that is easily accessible to users. The implementation of IoT technology in this system provides an innovative solution for increasing public awareness of the importance of clean water quality. With this system, it is expected to create a healthier and safer household environment for families.